2014
DOI: 10.1155/2014/698574
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR Gene C677T Polymorphism in Autism Spectrum Disorders

Abstract: Aim. Autism is a subgroup of autism spectrum disorders, classified as a heterogeneous neurodevelopmental disorder and symptoms occur in the first three years of life. The etiology of autism is largely unknown, but it has been accepted that genetic and environmental factors may both be responsible for the disease. Recent studies have revealed that the genes involved in the folate/homocysteine pathway may be risk factors for autistic children. In particular, C677T polymorphism in the MTHFR gene as a possible ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
(39 reference statements)
2
24
1
2
Order By: Relevance
“…Bugün için hastalık tanısı Amerikan Psikiyatri Birliği'nin Mayıs 2013'te tanı kriterlerini genişlettiği DSM-V'e (Diagnostic and Statistical Manual of Mental Disorders, 5 th edition) göre konmaktadır [4]. Hastalık etiyolojisinde genetik bir taban olduğu bilinmesine rağmen yapılan tüm çalışmalar hastalık patogenezini aydınlatmada yetersiz kalmıştır [5,6]. Otizmi anlamak adına yapılan genetik çalışmalar spesifik genlerdeki riskli varyantları tanımlayarak etiyolojide rol oynayan biyolojik mekanizmaları aydınlatmaya yöneliktir.…”
Section: Introductionunclassified
“…Bugün için hastalık tanısı Amerikan Psikiyatri Birliği'nin Mayıs 2013'te tanı kriterlerini genişlettiği DSM-V'e (Diagnostic and Statistical Manual of Mental Disorders, 5 th edition) göre konmaktadır [4]. Hastalık etiyolojisinde genetik bir taban olduğu bilinmesine rağmen yapılan tüm çalışmalar hastalık patogenezini aydınlatmada yetersiz kalmıştır [5,6]. Otizmi anlamak adına yapılan genetik çalışmalar spesifik genlerdeki riskli varyantları tanımlayarak etiyolojide rol oynayan biyolojik mekanizmaları aydınlatmaya yöneliktir.…”
Section: Introductionunclassified
“…There are various reports related to the prevalence of MTHFR C677T and A1298C polymorphisms in different study populations in Turkey (18)(19)(20)(21)(22)(23). Most of these studies are clinical series on different medical disorders (22,(24)(25)(26). In this short communication, we have aimed to demonstrate the allelic frequencies and the prevalence of homozygous MTHFR C677T and A1298C polymorphisms in patients that necessitated investigation of these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The MTHFR gene has been reported to increase the risk of birth defects such as neural tube defects and Down Syndrome [19,20]. Also, MTHFR polymorphism has been demonstrated to be associated with neurodevelopmental disorders such as schizophrenia and autism [21,22]. It has been shown that the MTHFR 677T allele might have an effect on the risk of schizophrenia in the Chinese Han population [23].…”
Section: Discussionmentioning
confidence: 99%